1994
DOI: 10.1093/nar/22.4.662
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular oligonucleotide hybridization detected by fluorescence resonance energy transfer (FRET)

Abstract: Fluorescence resonance energy transfer (FRET) was used to study hybrid formation and dissociation after microinjection of oligonucleotides (ODNs) into living cells. A 28-mer phosphodiester ODN (+PD) was synthesized and labeled with a 3' rhodamine (+PD-R). The complementary, antisense 5'-fluorescein labeled phosphorothioate ODN (-PT-F) was specifically quenched by addition of the +PD-R. In solution, the -PT-F/+PD-R hybrid had a denaturation temperature of 65 +/- 3 degrees C detected by both absorbance and FRET.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 23 publications
2
58
0
Order By: Relevance
“…S5B). Both strands were evenly distributed over the cytoplasm and showed an enhanced concentration inside the nucleus (26). An overlay of donor and acceptor images showed that the two strands colocalized.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…S5B). Both strands were evenly distributed over the cytoplasm and showed an enhanced concentration inside the nucleus (26). An overlay of donor and acceptor images showed that the two strands colocalized.…”
Section: Resultsmentioning
confidence: 91%
“…A BLAST search was performed with the sequence of the 16-mer to minimize specific interactions with genomic DNA or messenger RNA. Each strand was capped at both ends by an enantiomeric cytosine (L-nucleotide) (25) to suppress degradation by exonucleases (26). Lipofection was used for DNA delivery into the cells (26).…”
Section: Resultsmentioning
confidence: 99%
“…At different times after incubation of lipidic vectors with mouse serum at 37°C, an aliquot of sample was added to PBS to a final volume of 3 ml and the emission spectra were recorded between 500 and 650 nm with excitation at 470 nm and 10 nm excitation and 6 nm emission slits. 29 Sensitivity of DNA to mouse serum Lipopolyplexes or lipoplexes of different lipid compositions were prepared as described. They were then mixed with mouse serum at a ratio of 1:2 (v/v) and the mixtures were incubated at 37°C with gentle shaking.…”
Section: Fluorescence Resonance Energy Transfer (Fret)mentioning
confidence: 99%
“…Two days prior to injection, a confluent flask of Cos7 cells grown in Dulbecco modified Eagle medium supplemented with 10% fetal calf serum was trypsinized, diluted 1:6 or 1:12, and seeded onto 25-mmdiameter glass coverslips. Cells were mounted into a custom temperature-controlled chamber and placed atop an inverted microscope equipped with microinjection and video monitoring equipment and a confocal scanning laser module (28). Approximately 50 fl of BSA-peptide conjugate was injected into the nuclei of Cos7 cells.…”
mentioning
confidence: 99%